Penguatan Kelompok Pengrajin Gula Aren Di Desa Batulawang Melalui Digital Marketing dan Branding Produk Untuk Meningkatkan Pendapatan - Solandarika, Wulan; Permana, Nana Yudi; Mukhtar, Mukhtar; Aryansyah, Firman; Febriyani, Sarah; Ramdan, Dadan; Falendra, Randy Malik; Wahyudi, Jajang (Unri Conference Series: Community Engagement, 2025)
This community service program aims to address the main question of how digital marketing strategies and product branding can strengthen the capacity of palm sugar artisan groups in Batulawang Village while simultaneously increasing community income. The partner’s main challenges include limited product packaging, a lack of knowledge in digital marketing, and low product competitiveness in broader markets. The program was implemented using a participatory approach through the following stages: (1) identifying partner needs, (2) conducting digital marketing training, (3) providing assistance in designing packaging and brand identity, and (4) evaluating the application of marketing strategies. The results indicate improvements in artisans’ knowledge and skills in using digital media for promotion, the creation of palm sugar product branding with more attractive packaging, and an expansion of marketing reach to online platforms. The measurable initial impact includes an increase in product demand and a rise in the average income of artisan groups. Therefore, this program successfully strengthened community business capacity while also creating opportunities for more sustainable market development.